Development of a basic literacy module for adolescent mental health in school settings - Novianty, Anita; Rachel, Kathleen (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2024)
Adolescents are among the risk groups for mental health problems. The prevalence of these issues is rising annually. Delivering psychoeducation on mental health literacy, which addresses the ability to recognize mental health problems, as well as the referral mechanism for themselves and others when they have mental health problems, constitutes a way to prevent adolescents’ mental health problems. The purpose of this study is to use expert’s opinions to assess the content validity of primary mental health literacy modules. There are five modules: physical, emotional, cognitive, social, and mental health literacy. Five professionals, including clinical psychologists and teachers or staff at school, were involved in this study. The evaluation regarding modules’ contents was gathered using expert judgment sheets. Data analysis was performed using Aiken’s V. The results revealed a value range of 0.9-1.0, suggesting that experts acknowledged that all modules must be delivered to adolescents in school to promote their mental health. However, two comments must be considered in implementing this module, including inserting the reflection moment for students, improving the delivery method, and using popular language that adolescents frequently use.